Powstanie, rozwój i upadek komandorii templariuszy w Chwarszczanach = The establishment, the development and the fall of the templar commandery in Chwarszczany - Wasilkiewicz, Kamil (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Templars came to Poland in the 13th century on the initiative of the rivaling princes: Henry I the Bearded, Władysław Odonic and Barnim I. Thanks to the protection of these rulers, the order created 8 commandeties in the Pomerania, in Ziemia Lubuska, Great Poland and in Silesia.
Keywords: Zakon Ubogich Rycerzy Chrystusa i Świątyni Salomona; Chwarszczany - komandoria templariuszy